A model of early formation of uranium molecular oxides in laser-ablated plasmas. (6th November 2017) - Finko, Mikhail S; Curreli, Davide; Weisz, David G; Crowhurst, Jonathan C; Rose, Timothy P; Koroglu, Batikan; Radousky, Harry B; Armstrong, Michael R
Abstract: In this work, we present a newly constructed U x O y reaction mechanism that consists of 30 reaction channels (21 of which are reversible channels) for 11 uranium molecular species (including ions). Both the selection of reaction channels and calculation of corresponding rate coefficients is accomplished via a comprehensive literature review and application of basic reaction rate theory. The reaction mechanism is supplemented by a detailed description of oxygen plasma chemistry (19 species and 142 reaction channels) and is used to model an atmospheric laser ablated uranium plume via a 0D (global) model. The global model is used to analyze the evolution of key uranium molecular species predicted by the reaction mechanism, and the initial stage of formation of uranium oxide species.